Pressure pulses measurements as a way of determining reactor core barrel movements - Nordström, Christoffer (My University, 2012)
This work investigates if a movement of the core barrel in a pressurized water reactor may give rise to pressure pulses inside the reactor pressure vessel. The results are then evaluated with regards to which positions it would be best suitable to measure said pressure pulsation. The investigation is meant to conclude if it is plausible to use these pulsations to determine if the lower radial supports are working properly, securing the core barrel in place, stopping it from vibrating/moving. The lower supports have a maximum allowed gap between the clevis insert ant the lower radial support, this gap is known to be larger than intended but still below the upper allowed limit. If the gap would grow as large as it is allowed, would it should then be possible to measure this from the core barrel vibrations made possible from this gap. There are only certain positions where these measurements can be done, is it possible to se pressure pulses at these positions? From an initial heavily simplified model this seems to be the case, forcing vibrations with a certain frequency of the core barrel gives rise to a small fluctuation of about 0.009 MPa at the locations of interest. These pulsations show an almost linear relation between the core barrel displacement and peak to peak pressure amplitude. A more detailed model was used for the final simulation. This model confirms the results from the simplified model, showing a slightly larger pressure pulse in several of the guide tube positions. The peak to peak amplitude is about 0.002 MPa. The maximum fluctuations are occurring close to the periphery of the reactor pressure vessel, with both of the models. This suggests that it would be beneficial to measure the fluctuations at such a position.
Keywords: Energi; Fysik; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Energy; Physical Sciences; Sustainable Development; Innovation & Entrepreneurship